Urgensi Literasi Digital dalam Meningkatkan Kesiapan Kerja di Revolusi Industri 4.0 - Rahmat, Taufiq; Ashshiddiqi, M Taufan; Apriliani, Diah (The Journal of Society and Media, 2024)
The Industrial Revolution 4.0 and the COVID-19 pandemic changed the habits and workings of the business world and the industrial world with a digital technology approach, which has the potential to threaten various professions and employment opportunities. Graduates add to unemployment rates. Prospective workers need digital literacy competencies to compete in the current world of work. This study seeks to measure the extent and importance of digital literacy competence for the Gen-Z workforce of higher education graduates facing the world of work. This study uses an explanatory method with a sure approach. Data collection was done using a Likert scale 1-5 questionnaire, distributed to 133 respondents selected by the researchers, and targeted the workforce of college graduates aged 24-29 (Gen-Z) in the South West Java region with a simple random sampling technique. Then, the data were analyzed using descriptive analysis and structural equations, such as structural equation modeling. Digital literacy competence, including knowledge, skills, attitudes, and values, has a positive effect on the work readiness of Generation Z in rural South West Java. Further research is needed to develop human resources in these areas